Return to sport after total or unicompartmental knee arthroplasty: An informative guide for residents to patients - Dagneaux, Louis (EFORT Open Rev, 2017)
Knee arthroplasty survival rate — either UKA or TKA — is currently 95%, greater than it was ten years ago, but has not been specifically evaluated in very active patients practicing sport at a high intensity. The terms and conditions of return to physical activities are decided by the surgeon, the rehabilitation or Sports Medicine doctor, who needs to make sure that postoperative rehabilitation has been conducted optimally. Specifically, range of movement must be complete, muscular strengthening has to be sufficient and balance must be recovered by proprioception. Only after this stage (i.e. three to six months after surgery) can physical activities be resumed. Return to sport must be gentle and progressive, with moderate activities limited to short sessions. Progressively the patient will be able to return to intermediate activities, provided that he/she possesses the adequate level of technique for the sport. This up-to-date review for young surgeons and residents aims to provide an informative guide for patients regarding sport following knee arthroplasty. Cite this article: EFORT Open Rev 2017;2:496–501. DOI: 10.1302/2058-5241.2.170037